Mediation of Parents to Children on Media Consumption During The Covid-19 Pandemic - Raharjo, Galih Megah; Kusuma, Rina Sari (Universitas Muhammadiyah Surakarta, 2021)
Purpose : The purpose of this study is to find out how the mediation carried out by parents during the Covid-19pandemic on the use of gadgets by children. Methodology : This study employs a qualitative methodology that includes phenomenological studies and indepthinterviews with parents of elementary school-aged children. Result : This study employs the Parental Mediation Theory to generate three types of mediation: activemediation, restrictive mediation, and monitoring mediation. During a pandemic, many parents engage in activeand restrictive mediation with their children. In addition to using child-friendly language, parents also imposerules and restrictions on their children. Applications/Originality/Value: The use of parental mediation in the form of supervision, direction, and educationabout various things in an effort to mitigate the negative effects of using electronic devices.